Influence of mass-flow ratio of inner to outer secondary air on gas-particle flow near a swirl burner - Jing, Jianping; Zhang, Chunming; Sun, Wei; An, Jieruo; Bi, Jinsheng; Li, Zhengqi (Particuology, 2013)
The influence of mass-flow-rate ratio of inner to outer secondary air on gas-particle flow characteristics was determined in the near-burner region of a centrally fuel-rich swirl coal combustion burner, Velocity and particle volume flux profiles and normalized particle number concentrations were obtained. Peaks in tangential mean velocity and three-dimensional root-mean-square fluctuation velocities were found to decrease as the mass-flow-rate ratio increased. Moreover, the peaks in the mean axial velocities and parti- cle volume flux near the wall increased, whereas those near the chamber axis decreased. Simultaneously, both recirculation zone and swirl number decreased as the mass-flow-rate ratio increased.